Menjaga Tradisi, Mengasah Motorik: Dampak Positif Permainan Tradisional pada Siswa Sekolah Dasar - Melani Dewi Fatitah (WISE Pendidikan Indonesia, 2024)
Abstract This study aims to enhance the locomotor movement skills of fifth-grade students at Public Elementary School (SDN) 1 Waringinsari through the integration of traditional games within a Problem-Based Learning (PBL) framework. Employing a quasi-experimental design with a one-group pretest-posttest model, the research involved 25 students as its subjects. Data were collected using observation sheets that assessed eight aspects of locomotor movement skills, including movement coordination, body balance, and reaction speed. The findings revealed significant improvements across all measured aspects, with the average score increasing from 60 in the pretest to 85 in the posttest. This improvement underscores the effectiveness of traditional games, such as bakiak and enggrang, in enhancing students' motor skills. These results hold important implications for the development of a contextual and culturally relevant physical education curriculum, while also contributing to the preservation of traditional cultural heritage.